Management Accounting as Part of Enterprise Accounting (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article describes the concept of «management accounting», its main principles and functions. Studied the stages of development of management accounting, formed the main differences between management and financial accounting and options for communication between financial and management accounting. This publication proved the relationship financial and management accounting and studied foreign experience in accounting systems.The development of automation of production processes, increased competition, introduction of new management techniques, the use of computer technology for control and automation of accounting procedures promote the growth of the role of management accounting
Keywords: management accounting, financial accounting functions, principles, management, accounting system